Effect of Service Quality, Product Quality, Customer Satisfaction as Mediating Variable and Purchasing Decision on Pempek Ny Kamto Majapahit Semarang Restaurant - Ariefiantoro, Teguh; suryawardana, edy; Niati, Asih (Economics and Business Solutions Journal, 2021)
How the consequences of Service Quality, Product Quality, Consumer Loyalty as a Mediating Variable to Consumer Loyalty to purchasing decisions in Pempek Ny Kamto Majapahit Semarang. Respondents wore non-random sampling illustration methods. This illustration is wearing Purposive Sampling method, minimun once tasted Pempek Ny Kamto Semarang and the last time had arrived at Pempek Ny Kamto Majapahit Semarang. Methods of collecting information by wearing questionnaires and have been tested for validity and reliability. In testing variable Service Quality, Product quality, Consumer satisfaction with research Purchasing Decisions using multiple linear regression analysis. There are also results showing if Qualiy Service, Product Quality, Consumer Loyalty have a positive and significant influence on purchasing decisions.